Understanding Sexual Assault Survivors' Perspectives on Archiving Qualitative Data: Implications for Feminist Approaches to Open Science. (March 2023) - Campbell, Rebecca; Goodman-Williams, Rachael; Javorka, McKenzie; Engleton, Jasmine; Gregory, Katie
The open science movement has framed data sharing as necessary and achievable best practices for high-quality science. Feminist psychologists have complicated that narrative by questioning the purpose of data sharing across different paradigms, methodologies, and research populations. In these debates, the academic community has centered the needs and voices of researchers, and participants' perspectives are largely missing from this literature. In this study, we sought to understand how research participants feel about sharing qualitative data on a sensitive subject—sexual victimization. As part of a participatory action research project, we conducted qualitative interviews with sexual assault survivors about their post-assault help-seeking experiences. The federal funding agency that supported this project requires researchers to archive de-identified data in a national data repository (the National Archive of Criminal Justice Data [NACJD]). All participants consented to archiving data, and the vast majority expressed positive views about data sharing because they wanted to help other survivors. Participants emphasized that our participatory action research approach and our stated goal of helping survivors were important considerations in their decisions regarding data sharing. Researchers should obtain informed consent from their participants for data sharing/archiving, and discuss their dissemination plans during the informed consent process.